ANALYSIS OF THE WILLINGNESS TO PAY OF ADI SOEMARMO SURAKARTA INTERNATIONAL AIRPORT TRAIN USERS - Devanda Septian Putri Ariendani; Ibrahim Musa (Journal of Applied Economics in Developing Countries, 2022)
This study examines the magnitude of the probability value of passenger willingness to pay at the Adi Soemarmo International Airport in Surakarta and determines the factors that affect passenger willingness to pay based on the contingent valuation method approach. The results of this study obtained an average value of Willingness To Pay of IDR 13,765, with variables that affect the Willingness to pay for airport train tickets are age, facilities, services and income. These results are based on users' opinions of the Adi Soemarmo International Airport Train by looking at existing facilities and services and the economic situation of each individual.